Chronic total occlusions — Current techniques and future directions. (1st June 2015) - Touma, George; Ramsay, David; Weaver, James
Abstract: Chronic total occlusions (CTOs) of coronary arteries represent a common and significant challenge to interventional cardiology. Medical therapy is often regarded as an adequate long term strategy in the management of these lesions with surgical intervention for refractory symptoms. Extensive collateralisation is used as a marker of distal coronary perfusion, further reinforcing non-invasive strategies. This together with relatively low percutaneous success rates outside of specialised centres has meant that rates of percutaneous intervention have remained low. Increasing evidence suggests that CTOs are not a benign entity. Further, symptom control and quality of life improve significantly with successful percutaneous revascularisation. Both factors have reignited interest in percutaneous modalities. The Japanese have been pioneers in the field of CTO intervention although their success rates have been difficult to replicate. New techniques and equipment developed in North America offer an alternative to the Japanese approach. These techniques focus on time, radiation and contrast minimisation. This review will assess the histopathology of CTO and shifting paradigms in CTO treatment strategies. Highlights: Chronic total occlusions are common and prognostically important. Strategies for chronic occlusions are pioneered by Japanese, adapted by North American operators. Japanese and North American strategies appear divergent, both add considerable expertise.